2014
DOI: 10.7448/ias.17.1.18526
|View full text |Cite
|
Sign up to set email alerts
|

The case for addressing primary resistance mutations to non‐nucleoside reverse transcriptase inhibitors to treat children born from mothers living with HIV in sub‐Saharan Africa

Abstract: The prevalence of human immunodeficiency virus (HIV) drug resistance mutations (DRMs) was estimated in 25 untreated infants who were living with HIV-1, younger than 13 months and living in Senegal. Antiretroviral DRMs were detected in 8 of 25 (32%) children. Non-nucleoside reverse transcriptase inhibitor (NNRTI) DRMs were present in all (100%) children whose viruses harboured DRMs: K103N in 43%; Y181C, K101E and V106M each in 29%; and Y188L in 14%. The D67N thymidine-analogue mutation was observed in only two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[ 46 , 59 ] Our findings highlight the emergency of virological monitoring upon the usage of 1st-generation of NNRTIs, particularly in the children having NNRTI resistance mutations due to perinatal prophylaxis drugs. [ 12 , 101 103 ] Indeed, the lack of treatment monitoring by HIV-1 RNA load seems to delay the virological failure diagnosis, resulting in an increase in the duration of persisting viral replication under antiretroviral drugs pressure, and consequently the risk of accumulation of NNRTI mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 46 , 59 ] Our findings highlight the emergency of virological monitoring upon the usage of 1st-generation of NNRTIs, particularly in the children having NNRTI resistance mutations due to perinatal prophylaxis drugs. [ 12 , 101 103 ] Indeed, the lack of treatment monitoring by HIV-1 RNA load seems to delay the virological failure diagnosis, resulting in an increase in the duration of persisting viral replication under antiretroviral drugs pressure, and consequently the risk of accumulation of NNRTI mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Furthermore, if the extension of access to antiretroviral drugs in African children has significantly reversed the infant mortality curve associated with AIDS, it has also facilitated emergence and spread of drug-resistant virus in sub-Saharan Africa. [ 10 , 11 ] Various factors are involved in the fact that HIV-infected children and adolescents are more vulnerable than adults to virological failure and drug resistance including the HIV resistance risk during prevention of mother-to-child transmission, [ 12 ] frequently high HIV-1 RNA plasma level in children, [ 13 ] limited number of available pediatric-formulated antiretroviral drugs for the different age classes, variable pharmacokinetics, rapid changes in body weight, frequently observed poor adherence, social environment, psychosocial factors, and frequent absence of biological monitoring. [ 8 , 14 25 ] Thus, recent studies in African children receiving 1st-line antiretroviral treatment according to the treatment guidelines of the World Health Organization (WHO) for resource-limited countries have reported generally high degrees of virological failure depending in part on treatment duration, ranging from 6% in Kwazulu-Natal (South Africa), [ 26 , 27 ] 15% in Cape Town (South Africa), [ 28 ] 17% [ 29 ] to 44% [ 30 ] in Ghana, 26% in Uganda, [ 31 ] 29% in Rwanda, [ 32 ] 34% in Kenya, [ 33 ] 35% in Ivory Coast, [ 16 ] 40% in the Central African Republic, [ 23 ] 53% in rural Cameroon, [ 34 ] 55% in Senegal, [ 24 ] 56% in Togo, [ 25 ] 58% in Tanzania [ 35 , 36 ] to 61% in Mali.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of PDR we found, seems to fit in a trend of increasing PDR levels in sub-Saharan Africa. Early studies on paediatric PDR in PMTCT-unexposed children show a low prevalence of 0 to 2% [18Á20], while more recent studies conducted after 2010 report around 8% [21,22], and a South-African study from 2011 even found that 27 out of 75 unexposed children (36%) had PDR [23]. These paediatric data are in line with the increasing PDR prevalence in adults, correlating with the year of roll-out of national ART programmes and concomitant increased access to ARVs.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Available data in the sub-Saharan settings indicate that use of single-dose nevirapine (sdNVP), male gender, lower baseline immunological profiles, poor adherence, and breastfeeding are important predictors of HIVDR among children who have started on treatment. 12–14 The data on factors associated with the presence of HIVDR besides previous exposure to antiretroviral (ARV) among children before ART initiation are sparse, 15 , 16 yet baseline HIVDR is a critical indicator of the future success of ART as programs aim for universal access. The aim of this study was to evaluate the prevalence of and risk factors for primary HIVDR among newly diagnosed HIV-infected Ugandan children younger than 12 years.…”
Section: Introductionmentioning
confidence: 99%